2016
DOI: 10.1007/s12070-016-0967-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mode of Delivery and Hospital Type on Newborn Hearing Screening Results Using Otoacoustic Emissions: Based on Screening Age

Abstract: It is well known that false positive on newborn hearing screening increases cost and maternal anxiety and worry. We aimed to evaluate the influence of mode of delivery (cesarean, vaginal) and hospital type (private, public) on false positives first screening test based on screening age. Identification and control of these factors can reduce the rate of false positives. Overall, 2784 infants were evaluated by otoacoustic emissions test. Hearing screening test was performed before hospital discharge. Finally, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
10
2
Order By: Relevance
“…Our results show that the failure rate in the first OAE in VD infants is 1.5 fold higher than CD infants, which is similar to the Farahani ratio [ 34 ] who found that the failure rate was 15.5% in VD infants and 9.5% in CD infants. Likewise, Olusanya et al [ 24 ] stated that VD is associated with more than two-fold risk than a CD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results show that the failure rate in the first OAE in VD infants is 1.5 fold higher than CD infants, which is similar to the Farahani ratio [ 34 ] who found that the failure rate was 15.5% in VD infants and 9.5% in CD infants. Likewise, Olusanya et al [ 24 ] stated that VD is associated with more than two-fold risk than a CD.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, Xiao et al [ 35 ] found that 89 (21.0%) CD infants failed the first test out of 423 infants while 74 (7.1%) VD infants out of 1037 failed the test, which means that the rate of failure was 3 fold in CD infants; also Smolkin et al [ 21 ] found that failure rate was 3.2 higher in CD infants compared to VD infants (20.7% vs. 7.1%).Notwithstanding, in our analysis, the difference between CD and VD was not statistically significant with the failure rate of first OAE, which is similar to Güven [ 4 ] and Shahid [ 19 ] findings. On the contrary, previous studies reported that VD is a statically significant risk factor for first OAE failure [ 24 , 34 , 36 ]. Whereas others reported that CD appears to be a risk factor [ 21 , 35 , [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 79%
“…Tabrizi et al have also noted that for higher success rate, the first OAE test after cesarean delivery should be postponed [ 19 ]. In contrast to our finding, Farahani et al have demonstrate that false-positive OAE results in the vaginal delivery group was significantly higher than the cesarean group (15.5% vs. 9.5%) [ 20 ].…”
Section: Discussioncontrasting
confidence: 99%
“…They reported that the first screening with high false-positive results caused anxiety in the family and it would be important to perform the test at the 48 th hour postoperatively to reduce the cost [2]. On the other hand, Farahani et al showed that false positivity rates in hearing tests may be high in the early period owing to low tympanic membrane motility and fluid accumulation in the middle ear in the case of normal delivery [15]. In our study, cesarean deliveries without maternal-fetal risk factors were selected to exclude changes in the study group possibly due to the physical effects of the delivery method.…”
Section: Discussionmentioning
confidence: 99%